ANALISIS KESEHATAN POHON DI TAMAN RIA TAMAN KOTA DI KOTA BIMA - Purwidianti; Latifah, Sitti; Hidayati, Eni (Jurusan Kehutanan, 2022)
Urban Green Open Space (RTHKP) is part of the open space of an urban area filled with plants and plants to support ecological, social, cultural, economic and aesthetic benefits (Regulation of the Minister of Home Affairs Number 1, 2007). The interaction of urban forests with vehicle pollution in urban areas, not to mention the increasing population growth and climate instability, is currently feared to disrupt tree health. From the research, the results of the health status of trees in Taman Ria were, the number of trees in the Very Healthy category was 0 (0%) or none, the trees in the Healthy category were 4 (9%), the trees in the Less Healthy category were 22 (49%), sick category is 14 (31%) and very sick category is 5 (11%). It can be concluded that the trees in Taman Ria themselves fall into the Unhealthy category where the trees are vulnerable to being damaged in the future and if they are still exposed to pollution, weather and human treatment, they will exacerbate the damage.